Futuristas na Faculdade de Direito da Universidade de Coimbra. Décadas de 1910 e ded 1920 - Marnoto, Rita (2010)
(2010). Futuristas na Faculdade de Direito da Universidade de Coimbra. Décadas de 1910 e ded 1920, Foro das Letras, 19-20, 185-191. ISSN 0873 9552